Anxiety sensitivity and cannabis use motives among trauma‐exposed young adult cannabis users. Issue 3 (1st April 2022) - Short, Nicole A.; Evans, Mariah K.; Raudales, Alexa M.; Shapiro, Mary; Weiss, Nicole H.; Schmidt, Norman B.
Abstract: Background and Objectives: Anxiety sensitivity, or fear of anxious arousal, may be an important risk factor for problematic cannabis use. Specifically, anxiety sensitivity may motivate cannabis use to cope with distress, particularly among trauma‐exposed individuals. The current study tested associations among anxiety sensitivity, its subdomains, and cannabis use motives in a sample of trauma‐exposed cannabis users. We hypothesized elevated anxiety sensitivity, particularly cognitive concerns, would be associated with increased maladaptive coping use motives, after covarying for the number of traumas and cannabis use quantity. Method: Hypotheses were tested in a cross‐sectional study of trauma‐exposed young adult cannabis users (N = 56) ( M age = 20.7 years, 59% women, 73% white). Participants completed self‐report measures, and a clinical interview assessing cannabis use quantity. Results: Multiple regression analyses indicated that elevated anxiety sensitivity was associated with increased cannabis use coping motives, after covarying for the number of traumas experienced and cannabis use quantity. Specifically, higher levels of anxiety sensitivity cognitive and social concerns were associated with coping motives for cannabis use. Discussion and Conclusions: Anxiety sensitivity, particularly concerns about cognitive dyscontrol and negative social evaluations of anxious arousal, may motivate cannabis use to cope with stress among trauma‐exposed cannabis users. Future research should include prospective studies with diverse samples to replicate results and determine whether intervening on anxiety sensitivity could reduce maladaptive coping motives for cannabis use. Scientific Significance: The current study replicates prior research indicating anxiety sensitivity, particularly cognitive concerns, is associated with maladaptive cannabis use. Expanding on prior research, findings indicated anxiety sensitivity is associated with coping motives for cannabis use among trauma‐exposed cannabis users.